Effects of depsidones from Hypogymnia physodes on HeLa cell viability and growth - Stojanović, I. Ž; Najman, S; Jovanović, O; Petrović, G; Najdanović, J; Vasiljević, P; Šmelcerović, A (Folia biologica (Praha), 2014)
The anti-proliferative activitiy of Hypogymnia physodes methanol extracts (ME) and its main constituents, physodalic acid (P1), physodic acid (P2), and 3-hydroxy physodic acid (P3), was tested on human cancer HeLa cell lines. Three lichen depsidones, P1, P2 and P3, were isolated from H. physodes ME using column chromatography and their structures were determined by UV, ESI TOF MS, 1H and 13C NMR. The content of P1, P2 and P3 in ME was determined using reversed-phase highperformance liquid chromatography with photodiode array detection. P1-3 represented even 70 % of the studied extract. The HeLa cells were incubated during 24 and 72 h in the presence of ME and depsidones P1, P2 and P3, at concentrations of 10-1000 μg/ml. Compounds P2 and P3 showed higher activity than compound P1. Half maximal inhibitory concentrations (IC50, μg/ml) of P1, P2, P3 and ME for 24-h incubation were 964, 171, 97 and 254 μg/ml, respectively, while for 72-h incubation they were 283, 66, 63 and 68 μg/ml. As far as we know, this is the first report on the effect of H. physodes ME and their depsidones on HeLa cells.
Keywords: lišejníky; depsidy; HeLa Cells; laktony; lidé; HeLa buňky; Cell Survival; viabilita buněk; inhibiční koncentrace 50; Inhibitory Concentration 50; Lactones; Depsides; Lichens; Humans